MAMPUKAH ANGGARAN MENGENDALIKAN DEFORESTASI DI KAWASAN KONSERVASI? - Resi Diniyanti; Alin Halimatussadiah (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
One of the main objectives of the establishment of a conservation area is to preserve the ecosystem and biodiversity. Even in many countries around the world, including Indonesia, the establishment of conservation areas has become the government's alternative strategy for protecting and maintaining biodiversity resources. The government allocates budget for conservation areas, but in some locations degradation and deforestation still persist. It is therefore important to evaluate the commitment of the government to the protection of biodiversity, one of which is the rate of deforestation. This study aims to examine whether government spending has impact to control deforestation in conservation areas in Indonesia. Utilizing a dynamic panel model with a Generalized Method of Moment (GMM) estimation, this study uses the forest cover data in 43 national parks that lies in 114 districts/cities during 2013-2017. The results show that the government spending for forest protection activities and forest ranger has an effect on controlling the deforestation rate in conservation area. However, there is no evidence showing correlation between the spending for community empowerment to deforestation control. This indicates that the government should consider budget allocation to make deforestation control more effective.